(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The study aimed to know the attitudes of male and female primary education teachers towards the integration of people with special needs in the regular classes, and to know the differences in the integration of people with special needs in the regular classes according to the variable of gender and professional seniority. School integration after verifying its psychometric characteristics, and the data processing was relied on the statistical package program for social sciences (SPSS). Primary education towards the integration of people with special needs in the regular classes according to the variable of sex, as well as the presence of differences in the attitudes of primary education teachers towards the integration of people with special needs in the regular classes according to the variable of professional seniority.Keywords: integration - trends, primary education, teacher, people with special needs